Enhancing Lubrication System Efficiency in Marine Diesel Engines with Centrifugal Separators - a Case Study Of LPG/C Arimbi: Technical and Cost-Effective Perspectives - Tuswan Tuswan; Muhammad Fuad Rasyad; Untung Budiarto; Ocid Mursid; Andra Tanzani; Serliana Yulianti; Abdi Ismail; Rizky Chandra Ariesta (Universitas Sebelas Maret, 2024)
The lubrication system in an engine is critical for reducing friction between components, preventing wear, reducing heat, protecting components from deposits, and sealing. Maintaining and extending the life of lubricants is crucial for lowering lubricant usage costs. A centrifugal separator is an auxiliary machine that cleans and separates two insoluble liquids with different densities. This study aims to evaluate the efficiency of lubricant life, lubricant usage cost savings, and return on investment time for a centrifugal separator. The study uses a case study of LPG/C Arimbi, where a centrifugal separator has helped maintain lubricants, prevent wear, and separate fuel and free water from lubricants. The centrifugal separator can also maintain Total Base Number (TBN) and viscosity values by filtering solid particles or wear elements up to a size of 0.5 µm. The study found that the difference in lubricant life was 11,780 hours, and the cost savings obtained were IDR 186,456,666 per year. The return on investment time for purchasing a centrifugal separator is three years and two months, assuming an average working hours of LPG/C Arimbi every year of 3,660 hours. Therefore, using a centrifugal separator can improve the efficiency of lubricant life and reduce lubricant usage costs, providing a positive return on investment in the long run.